Tomographic profile of patients attended with brain vascular accident in an emergency hospital in Teresina – PI (Research, Society and Development, 2021)
The objective of this study was to know the most prevalent tomographic and epidemiological pattern of patients admitted with a stroke at the Emergency Hospital of Teresina - HUT in 2020. This is an epidemiological, quantitative observational, cross-sectional study. retrospective, performed by collecting data from electronic medical records. The results revealed that, of the 384 cases, 73.6% had ischemic CVA (iCVA), the brain region most affected in CVAi was the fronto-parietal region with 36.4% of the cases and in CVA the parietotemporal region with 28 .7%. The main risk factors were Hypertension (62.5%) and Diabetes Mellitus (31.2%). The time interval between patient admission and the performance of Computed Tomography (CT) ranged from 30min to 3h. Of the interventions, only 3% used thrombolytics. From the results, it can be concluded that the profile of the studied population does not differ from that usually found in the literature and that there was difficulty in determining the time of onset of symptoms and, therefore, the indication for thrombolytic therapy.